Analsisis Perbandingan Tantangan Audit Syariah di Indonesia dan Turki - Putra, Febrian Maulana; Suryanto, Tulus; Hilal, Syamsul; Hanif; Fasa, Muhammad Iqbal (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to investigate and compare the challenges faced in the implementation of sharia audits in Indonesia and Turkey. Sharia audits play an important role in ensuring financial institutions' compliance with Islamic economic principles, and comparisons between these two countries can provide in-depth insights into the complexities of Islamic audits across multiple contexts. The research method used is comparative descriptive, by evaluating previous research findings and relevant sources. Analysis is carried out on scientific literature, including from journals, books and other sources. Through this approach, the research will identify key challenges faced by sharia auditors, such as regulatory differences, public understanding of sharia principles, and economic policies affecting financial institutions. By comparing the results of research between Indonesia and Turkey, this study is expected to provide recommendations to improve the effectiveness and efficiency of sharia audits in both countries. The results of this study can also contribute to the development of Islamic audit practices globally, taking into account contextual and cultural differences between countries. In conclusion, this research is expected to provide a better understanding of the challenges of sharia auditing in Indonesia and Turkey, as well as contribute to the development of more effective sharia audit methods and practices in the future.